Efektivitas belajar online dari rumah (daring) terhadap Proses pembelajaran yang mengacu kepada Standar Nasional Pendidikan Tinggi (SN-DIKTI) di Pandemi Covid 19 - Erny Melina; Henky Setiady (J-MAS (Jurnal Manajemen dan Sains), 2022)
The result obtained from the descritive analysis test by categorizing into the level of closeness relation through the value of the contingency coefficient indicate that the effectiveness of online learning from home has a fairly effective value, consisting indicators of accuracy in mastering behavior, the speed of performance, the conformity with procedures, the quantity of performance and the quality of the final result, and the learning process variables that refer to The National Higher Education Standards (SN-DIKTI) also have fairly effective value consisting of interactive, integrative, scientific, contextual, thematic, effective, collaborative, and student-centered indicators. The chi-square test that has done with SPSS version 24, shows that the ralation or closeness and significance, of the online learning effectiveness variable from home with The learning process variable reffering to SN-DIKTI, with a significance value or Asymp.Sig.(2-tailed) on the Pearson Chi-Square test is 0,000. This is shows that the value of Significance or Asypm.Sig.(2-tailed) 0,000 < 0,005. It can be concluded there is a relation between the effectiveness of online learning from home with The learning process to The National Higher Education Standards (SN-DIKTI) with the Contingency Coefficient (value) at 0,720.